2018
DOI: 10.1101/344234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete Disruption of Autism-Susceptibility Genes by Gene-Editing Predominantly Reduces Functional Connectivity of Isogenic Human Neurons

Abstract: Co-corresponding and senior authors: singhk2@mcmaster.ca, jellis@sickkids.ca, stephen.scherer@sickkids.ca (lead contact) SummaryAutism Spectrum Disorder is phenotypically and genetically heterogeneous, but genomic analyses have identified candidate susceptibility genes. We present a CRISPR gene editing strategy to insert a protein tag and premature termination sites creating an induced pluripotent stem cell (iPSC) knockout resource for functional studies of 10 ASD-relevant genes (AFF2/FMR2, ANOS1, ASTN2, ATRX,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…Using overexpression of NEUROG1 and NEUROG2, the authors differentiated the cell line into a network of both glutamatergic excitatory and GABAergic inhibitory neurons. Similarly to what Deneault et al reported with SCN2A −/− neurons [83], Lu et al found that SCN2A +/− neurons also displayed a significant reduction in spontaneous neural activity. However, SCN2A haploinsufficiency did not appear to disrupt inhibitory synaptic transmission in GABAergic cells.…”
Section: Cell-based Scn2a Models Human Stem Cell Models Of Scn2a Mutasupporting
confidence: 63%
See 2 more Smart Citations
“…Using overexpression of NEUROG1 and NEUROG2, the authors differentiated the cell line into a network of both glutamatergic excitatory and GABAergic inhibitory neurons. Similarly to what Deneault et al reported with SCN2A −/− neurons [83], Lu et al found that SCN2A +/− neurons also displayed a significant reduction in spontaneous neural activity. However, SCN2A haploinsufficiency did not appear to disrupt inhibitory synaptic transmission in GABAergic cells.…”
Section: Cell-based Scn2a Models Human Stem Cell Models Of Scn2a Mutasupporting
confidence: 63%
“…However, a number of investigators have used CRISPR to genetically modify the SCN2A gene in stem cells derived from control subjects, which have revealed phenotypes that mirror those observed in mouse models of SCN2A syndrome mentioned above. In 2018, Deneault et al used CRISPR to create a homozygous knockout of SCN2A in a human iPSC line generated from the unaffected father of a child with ASD [83]. These stem cells were subsequently differentiated into excitatory neurons through ectopic expression of NEUROG2 and assessed for neural activity.…”
Section: Cell-based Scn2a Models Human Stem Cell Models Of Scn2a Mutamentioning
confidence: 99%
See 1 more Smart Citation
“…1C) that may hint at a common pathological mechanism that impairs plasticity of a neural circuit's decision to respond without altering response vigor. Indeed, these Drosophila and C. elegans results may reflect a behavioral outcome of circuit-level hyperexcitability recently discovered in several human iPSC-derived neuronal culture models of a number of monogenic ASD risk factors (71,72). The results also provide a potentially plausible explanation for inconsistent reports of impaired habituation in humans, which variably employ diverse response metrics most often without genetic stratification of patient populations (15,39).…”
Section: Discussionmentioning
confidence: 67%
“…The results also provide a potentially plausible explanation for inconsistent reports of impaired habituation in humans, which variably employ diverse response metrics most often without genetic stratification of patient populations (15,39). While these shared phenotypes are exciting, our results and those of several other model systems (11,15,19,22,70,71) reveal a remarkable diversity in phenotypic disruptions, suggesting that single phenotype functional validation and characterization efforts will be insufficient to capture the complex multifaceted phenotypic disruptions that stem from mutations in ASD-associated genes.…”
Section: Discussionmentioning
confidence: 85%